Objective assessment of induced acute pain in neonatology with the Newborn Infant Parasympathetic Evaluation index. (24th March 2018) - Cremillieux, C.; Makhlouf, A.; Pichot, V.; Trombert, B.; Patural, H.
Abstract: Background: Objective tools are needed to improve pain assessment in newborns. The aim of this study was to assess the correlation between the Newborn Infant Parasympathetic Evaluation (NIPE) index and two pain scales during a painful procedure in premature infants. Method: Each baby born at least at 26 weeks of gestational age (GA) undergoing a planned painful procedure in the Neonatal Intensive Care Unit (NICU) was eligible. NIPE index, heart rate variability (HRV) indices and Neonatal Acute Pain scale (DAN) were recorded across three periods: the first at rest 5 min before the painful procedure (T1), the second during it (T2) and the third 3 min after the end of it (T3). The Premature Infant Pain Profile‐Revised (PIPP‐R) pain scale was recorded at T2. Results: Sixty‐four recordings were performed in 29 preterm infants (mean GA = 29.9 ± 4.2 weeks). Twenty‐eight tachograms were coupled to NIPE for analysis. We did not find a correlation between the NIPE index and DAN and PIPP‐R at the pain time T2. Between T1 and T2, heart rate was higher (159 ± 16 vs. 169 ± 12, p < 0.001). Considering the linear HRV indices, we did not observe a modification in parasympathetic or sympathetic activity, while for the nonlinear HRV indices (H exponent, Approximate and conditional Entropy), a significant change towards a loss of physiological chaotic cardiac behaviour was detected. Conclusions: The NIPE index seems to be not reliable to assess acute pain in the preterm infant, but other HRV indices could be explored as additional tools next to pain scales in NICUs. Significance: The NIPE monitor was developed for objective pain assessment in neonates based on HFnu variations, but it does not seem reliable enough for assessing acute pain in real time in preterm neonates. Pain assessment in preterm babies still relies on pain scales.